Campaign individualization in a comparative perspective: does the context matter? - Marco Lisi (História - Revista da Faculdade de Letras da Universidade do Porto, 2019)
Despite a great flourishing of studies on election campaigns, the issue of individualized campaigns has been widely neglected, especially from a comparative perspective. Yet, campaigns differ not only in terms of strategy or style, but also with regard to the role played by individual candidates. This article examines the variation of both the communicative focus and the resources used by candidates across different Western democracies. Using data from the Comparative Candidate Surveys (CCS), it tests the impact of several institutional and political features on campaign individualization. Our results show that both electoral systems and the legal framework regulating electoral contests display a significant impact on campaign individualization.